Recurrent Stroke. Issue 9 (September 2015) - Andersen, Søren Due; Gorst-Rasmussen, Anders; Lip, Gregory Y.H.; Bach, Flemming W.; Larsen, Torben Bjerregaard
<x xml:space="preserve">Abstract</x> Background and Purpose— The CHA2DS2VASc score and the Essen Stroke Risk Score are respectively used for risk stratification in patients with atrial fibrillation and in patients with cerebrovascular incidents. We aimed to test the ability of the 2 scores to predict stroke recurrence, death, and cardiovascular events (stroke, transient ischemic attack, myocardial infarction, or arterial thromboembolism) in a nationwide Danish cohort study, among patients with incident ischemic stroke and no atrial fibrillation. Methods— We conducted a registry-based study in patients with incident ischemic stroke and no atrial fibrillation. Patients were stratified according to the CHA2DS2VASc score and the Essen Stroke Risk Score and were followed up until stroke recurrence or death. We estimated stratified incidence rates and hazard ratios and calculated the cumulative risks. Results— 42 182 patients with incident ischemic stroke with median age 70.1 years were included. The overall 1-year incidence rates of recurrent stroke, death, and cardiovascular events were 3.6%, 10.5%, and 6.7%, respectively. The incidence rates, the hazard ratios, and the cumulative risk of all outcomes increased with increasing risk scores. C-statistics for both risk scores were around 0.55 for 1-year stroke recurrence and cardiovascular events and correspondingly for death around 0.67 for both scores. Conclusions— In this cohort of non–atrial fibrillation patients with incident ischemic stroke, increasing CHA2DS2VASc score and Essen Stroke Risk Score was associated with increasing risk of recurrent stroke, death, and cardiovascular events. Their discriminatory performance was modest and further refinements are required for clinical application.